Longitudinal case study of fixed revenue accounting at a Japanese semiconductor distributor / Kenichi Suzuki, Kohsuke Matsuoka and Hiromune Ishii. - Suzuki, Kenichi; Matsuoka, Kohsuke; Ishii, Hiromune (Accounting Research Institute and UiTM Press, Universiti Teknologi MARA, 2017)
Fixed revenue accounting (FRA) is a management control system for relationship marketing strategy. Although FRA has been investigated among some Japanese companies since it was proposed in 2005, there has not been any study examining the effects FRA has on employees' awareness and behaviors based on longitudinal investigation. In this paper, we state a longitudinal case study about FRA at a Japanese semiconductor distributor during 2006-2014. We found that at Company A, only senior management used FRA to understand its strategy until 2012. After they became convinced FRA could guide relationship marketing, they started using FRA as a management control system in 2013 by binding it with its strategic plan and annual budgets. We interviewed with twelve core employees in 2014 and clarified that FRA motivated employees to accept relationship marketing strategy, deepened common understanding between departments, and facilitated an understanding of how to achieve goals.